Efektivitas Mutasi Transformator Dalam Mengatasi Fluktuasi Beban Pada Trafo Distribusi ULP Bululawang - Harrij Mukti K.; Rachmat Sutjipto; Vidiasih (Elposys: Jurnal Sistem Kelistrikan, 2024)
Transformer is a very important component in the distribution of electricity from the distribution substation to consumers. Overloading and underloading of transformers can lead to significant inefficiencies and increased losses in the electrical distribution system. Based on data measurement of the ULP Bululawang transformer in 2022, it was found that the C0177 transformer (100 KVA) was overloaded (88.4%) and the C0254 transformer (160 KVA) was underloaded (21.4%). Load forecasting for 2027 predicts that the C0177 transformer load will reach 107%, causing overheating, while the C0254 transformer will remain underloaded at 23.68%. To address these issues, a transformer mutation was proposed. This study aims to evaluate the effectiveness of transformer mutation in redistributing loads and improving efficiency. The method involved measuring transformer loads before and after mutation and using the Least Square method for load forecasting. Post-mutation measurements showed the C0177 transformer load reduced to 62.6% and the C0254 transformer load increased to 37%. These results indicate that the transformer mutation significantly balanced the load distribution. The study also adjusted the protection settings, including FCO, output cable, main switch, PHB-TR, and NH Fuse output cable. The findings suggest that transformer mutation can effectively address load imbalances, improve operational efficiency, and reduce power losses in the distribution system.